2013
DOI: 10.1021/cm303096e
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Structural Changes and Gas Evolution during the Thermal Decomposition of Charged LixNi0.8Co0.15Al0.05O2 Cathode Materials

Abstract: In this work, we present results from the application of a new in situ technique that combines time-resolved synchrotron X-ray diffraction and mass spectroscopy. We exploit this approach to provide direct correlation between structural changes and the evolution of gas that occurs during the thermal decomposition of (over)charged cathode materials used in lithium-ion batteries. Results from charged Li x Ni0.8Co0.15Al0.05O2 cathode materials indicate that the evolution of both O2 and CO2 gases are strongly relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
260
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(276 citation statements)
references
References 47 publications
12
260
1
3
Order By: Relevance
“…In other words, the NMC structure is thermodynamically unstable at high degrees of delithiation, and only retains its oxygen and its layered bulk structure due to the kinetically hindered oxygen diffusion. This hypothesis is supported by the literature, where it is reported that layered NMC 21,25,27,70,71 and NCA 22,25,26,70 structures in the charged state (low lithium content) are not stable at high temperatures (> 170…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In other words, the NMC structure is thermodynamically unstable at high degrees of delithiation, and only retains its oxygen and its layered bulk structure due to the kinetically hindered oxygen diffusion. This hypothesis is supported by the literature, where it is reported that layered NMC 21,25,27,70,71 and NCA 22,25,26,70 structures in the charged state (low lithium content) are not stable at high temperatures (> 170…”
Section: Discussionsupporting
confidence: 75%
“…5) and a layered to rock-salt (Eq. 6) transformation using, in analogy to the literature, 21,22,36,83 the following general equations with M = (Ni, Mn, Co):…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44][45] Hwang and coworkers studied the correlation between the gas evolution and phase transition in highly delithiated nickel-rich cathode by conducting combined in situ time resolved-X-ray diffractometer with mass spectroscopy (MS). [46] The points that phase transition occurs (from layered structure to spinel structure and from spinel structure to rock salt structure) precisely coincided with the oxygen gas release peaks. Furthermore, at temperature over 320 °C, the carbon dioxide was formed.…”
Section: Phase Transitionmentioning
confidence: 74%
“…10 Such chemically driven spinel and/or rocksalt formation have been shown and intensively characterized for the thermally induced transformation of partially delithiated NCMs. 52,53 The general chemical reaction for spinel formation is given in Equation 3. Since rocksalt structures could not be observed by HRTEM measurements (see Figure 7 and Figure 8), the surface layer thickness is estimated only assuming the formation of a spinel surface layer.…”
Section: Discussionmentioning
confidence: 99%